Facile Growth Of Carbon Nanaotube Electrode From Electroplated Ni Catalyst For Supercapacitor - Visittapong Yordsri; Winadda Wongwiriyapan; Chanchana Thanachayanont (My University, 2015)
A facile growth of carbon nanotubes (CNTs) was facilitated by the use of direct-current plating technique for catalyst preparation. Ni nanoparticles (NPs) were deposited on Cu foil at different applied voltages of 1.0, 1.5 and 2.0 V. The Ni-deposited foil was subsequently used as catalyst for CNTs synthesis by chemical vapour deposition (CVD) method. CVD was carried out at 800 ºC using ethanol as carbon source. A voltage of 1.5 V was the optimum condition to deposit uniform Ni NPs that had a narrow size distribution of 55±3 nm, which in turn, yielded synthesized CNTs with a uniform diameter of approximately 60±5 nm with graphitic layers parallel to the CNTs axis. On the other hand, electroplated Ni at 1.0 V produced CNTs with graphitic layers at an angle to the CNTs axis, while electroplated Ni at 2.0 V produced curly CNTs with a wide distribution of diameters. These results show that Ni NPs size distribution could be controlled by electroplated voltage. Our observation was that Ni NPs with a narrow distribution of sizes and a uniform diameter is a key to uniform CNT synthesis. Furthermore, the synthesized CNTs electrode shows a faradic pseudo capacitance property, which can be attributed to the existence of oxidized Ni NPs. These results propose that the synthesized CNTs are promising materials for future super capacitor application. The optimization of ratio of Ni NPs and CNTs may improve the supercapacitors performance.
Keywords: Supercapacitor Materials and Fabrication